2022
DOI: 10.1007/s10989-021-10347-0
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya Virus Vaccine Development: Through Computational Proteome Exploration for Finding of HLA and cTAP Binding Novel Epitopes as Vaccine Candidates

Abstract: Chikungunya virus is a major arbovirus of great public health concern in the whole world, but no vaccine is yet available, still advance therapeutic treatment and effective vaccines are in progress. The present multistep screening and structural binding analysis with CHIKV proteome exploration can be crucial in the development phase of CHIKV epitope based vaccine. The approach employed in two phases (i) Sequence based screening of peptides through propred and IEDB Server (ii) Structure based study through auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Also, docked complex was analysed for simulation analysis, and it was found that they show stable interaction pattern as per the RMSD and RMSF plots. Many previous studies show the importance of immunoinformatic study to support our analysis on fungal epitope determination likewise for Candida auris, Tropheryma whipplei [21,22], dengue [23], human cytomegalovirus [24], and chikungunya [25]. Modern chemi-informatic and immunoinformatics study not only supports rapid vaccine prediction but also provides efficient economic resource management [26][27][28], although immunoinformatic requires wet-lab support as future perspectives for epitope synthesis and animal cell line-dependent validations.…”
Section: Discussionsupporting
confidence: 56%
“…Also, docked complex was analysed for simulation analysis, and it was found that they show stable interaction pattern as per the RMSD and RMSF plots. Many previous studies show the importance of immunoinformatic study to support our analysis on fungal epitope determination likewise for Candida auris, Tropheryma whipplei [21,22], dengue [23], human cytomegalovirus [24], and chikungunya [25]. Modern chemi-informatic and immunoinformatics study not only supports rapid vaccine prediction but also provides efficient economic resource management [26][27][28], although immunoinformatic requires wet-lab support as future perspectives for epitope synthesis and animal cell line-dependent validations.…”
Section: Discussionsupporting
confidence: 56%
“…This examination not just give experiences about characteristic and mutational determination pressures acting at genomic levels of T. whipplei yet besides offer a superior cognizance of transformative improvements in this host-versatile bacterium. This computational examination uncovered the data concerning profoundly translated proteins and enzymes of this bacterium, and the conceivable amino acids that can be considered in epitope-based prophylaxis plan to get the inhibitory effect on bacterial action on its host or to create a better conceivable treatment like in immunoinformatics-based recent studies [ 14 , 15 ]. Ribosomal RNA (16S and 23S) codon usage patterns were analyzed here to determine the changes associated with evolutionary or phylogenetic patterns of the bacterium.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Rahatgi’s group from IITR provided a discernment of CHIKV E2-FL protein immunogenic epitopes, which can be used for the development of novel multiepitope-based anti-CHIKV vaccine strategies [ 211 ]. Kumar’s team conducted an in silico study for the development of a CHIKV epitope-based vaccine as well as diagnostic development [ 212 ]. Sreekumar and colleagues reported through another recent study the probable application of an attenuated CHIKV strain RGCB355/KL08-p75 as a probable candidate for vaccine development [ 213 ].…”
Section: Chikv Research: Indian Scenariomentioning
confidence: 99%